Development of management accounting functions in the corporate governance system - S. N. Grichkina; K. S. Chestnova (Учёт. Анализ. Аудит, 2023)
Problematic issues of the development of theory of management accounting in context of improving corporate governance and increasing requirements from various stakeholders to its information support are increasingly becoming the object of research by domestic and foreign scientists. The purpose of this study is to identify the trends in the development of management accounting in the conditions of digitalization of the economy, and the transformation of business processes under the influence of changes in business environment as well as justification and substantiation of the new functions of management accounting in connection with the changing requirements of corporate governance and the need to improve its information support. To achieve this goal, the methods of synthesis and analysis, abstraction, deduction and induction, comparison and systematization were used, as well as a critical analysis of existing views on the essence of management accounting, its functions and possible development scenarios, taking into account transformations in accounting science and practice observed in the third decade of the XXI century. In the process of work the results of own researches conducted and received within the framework of the scientific school of the Financial University “Accounting-analytical and control processes of economic subjects of information society” and in the course of practical activity of the authors were used. Based on the analysis of literary sources, the requirements of national and international standards in the field of both accounting and financial reporting and in sustainable development, current accounting practices and corporate governance practices, new management accounting functions have been identified and justified, the implementation of which is aimed at the formation and presentation of better quality data and information as part of corporate reporting with predictive value. The results obtained can be used by economic entities in optimizing accounting and control processes and developing internal regulations on management accounting, as well as by accounting regulatory entities and professional organizations in developing recommendations in the field of management accounting for various economic entities.